Protecting traditional healing practices in Malawi : are there lessons to be learnt from South Africa? - Kotey, Nii Ashie (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2005.